The Two Faces of Competition: Dynamic Resourcefulness and the Hypercompetitive Shift - Thomas, L.G. (Organization Science, 1996)
Competition in the American economy has fundamentally changed over the last few decades, from static to dynamic. This study labels this important change the hypercompetitive shift, and documents it across 200 industries of the US manufacturing sector during I958 to 1991. For industries that undergo a hypercompetitive shift, there is an increase in the cross-firm variance in performance and a rotation in the value-rivalry relationship from a negative association to an inverted-U. As a consequence of these competitive changes, the strategic focus of firms shifts from careful exploitation of given, highly durable strategic assets to the steady creation of many new, rapidly depreciable ones. The key driver of hypercompetitive shift is the dynamic resourcefulness of an industry, or the ease with which new strategic assets can be created. Determinants of dynamic resourcefulness include the dynamism of related transactors (notably consumers and suppliers). the knowledge base of the industry, and structural conditions that promote easy entry.